Antara Analogia Fidei dan Analogia Antecedents: Analisis Hermeneutika Walter C. Kaiser, Jr. dalam Dialog dengan Hermeneutika Pentakostal - Kurniawan, Otniel Kharisma Yudhistira; Situmorang, Jonar (Jurnal Teologi Berita Hidup, 2025)
This article is written to examine the hermeneutical approach of Walter C. Kaiser, Jr., in his critique of the use of analogy of faith (analogia fidei) as the main interpretive tool in biblical theology. Kaiser proposed Analogia Antecedents as an alternative to interpreting the Bible based on previously revealed texts chronologically. The aim is to maintain the historical intent and the true intent (authoritative) of the original author. The research in this article uses a qualitative literature study method with a comparative analysis approach to Kaiser's main works and hermeneutical literature from the Pentecostal tradition. Through comparative analysis, it was found that both still adhere to the authority of the Bible, but both offer different heuristic methodologies in interpreting the text, where one emphasizes the structure of progressive revelation, while the other gives place to pneumatological experience. The conclusion obtained is that these two approaches have their respective strengths and limitations, but both open up opportunities for rich integration between faithfulness to the text and sensitivity to the role of the Holy Spirit in biblical interpretation.